2021
DOI: 10.12659/ajcr.930573
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis-Associated Acute Perimyocarditis with Cardiogenic Shock: A Case Report

Abstract: Patient: Female, 21-year-old Final Diagnosis: Toxocariasis-associated acute perimyocarditis with cardiogenic shock Symptoms: Dizziness • epigastric pain • headache • vomiting Medication: — Clinical Procedure: — Specialty: Cardiology Objective: Rare disease Background: Toxocariasis is an infection due to ingestion of the helminth parasite larvae found in dogs ( Toxocara canis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Serum immunoglobulin E levels were elevated (1650 unit/mL) Tender nodules and worm-like live organisms were observed in her upper arms and shoulders. cysticercosis IgG(+) Albendazole (400 mg/d) for 3 days Telephonic follow-up 1 month later indicated that the blood eosinophilia and pleural effusion were resolved Park et al [ 13 ] 21/female Korean Toxocariasis None Epigastric pain, vomiting, headache, and dizziness Right pleural effusion, pericardial effusion, and focal ascites in the pelvic cavity. Laboratory tests revealed an elevation of eosinophils (40%) and cardiac enzymes (creatinine kinase-MB 27.6 ng/mL, high-sensitive cardiac troponin T 1.21 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Serum immunoglobulin E levels were elevated (1650 unit/mL) Tender nodules and worm-like live organisms were observed in her upper arms and shoulders. cysticercosis IgG(+) Albendazole (400 mg/d) for 3 days Telephonic follow-up 1 month later indicated that the blood eosinophilia and pleural effusion were resolved Park et al [ 13 ] 21/female Korean Toxocariasis None Epigastric pain, vomiting, headache, and dizziness Right pleural effusion, pericardial effusion, and focal ascites in the pelvic cavity. Laboratory tests revealed an elevation of eosinophils (40%) and cardiac enzymes (creatinine kinase-MB 27.6 ng/mL, high-sensitive cardiac troponin T 1.21 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women who are infected with toxocariasis are at risk of adverse outcomes for both themselves and their unborn babies such as miscarriage, stillbirth, birth defects, and damage to internal organs, especially eyes and brain [11][12][13]. Also, toxocariasis rarely causes perimyocarditis with cardiogenic shock [14,15].…”
Section: Introductionmentioning
confidence: 99%